Molecular and evolutionary basis for survival, its failure, and virulence factors of the zoonotic nematode Anisakis pegreffii - Trumbić, Željka; Hrabar, Jerko; Palevich, Nikola; Carbone, Vincenzo; Mladineo, Ivona (Genomics, 2021)
Parasitism is a highly successful life strategy and a driving force in genetic diversity that has evolved many times over. Accidental infections of non-targeted hosts represent an opportunity for lateral host switches and parasite niche expansion. However, if directed toward organisms that are phylogenetically distant from parasite's natural host, such as humans, it may present a dead-end environment where the parasite fails to mature or is even killed by host immunity. One example are nematodes of Anisakidae family, genus Anisakis, that through evolution have lost the ability to propagate in terrestrial hosts, but can survive for a limited time in humans causing anisakiasis. To scrutinize versatility of Anisakis to infect an evolutionary-distant host, we performed transcriptomic profiling of larvae successfully migrating through the rat, a representative model of accidental human infection and compared it to that of larvae infecting an evolutionary-familiar, paratenic host (fish). In a homeothermic accidental host Anisakis upregulated ribosome-related genes, cell division, cuticle constituents, oxidative phosphorylation, in an unsuccessful attempt to molt to the next stage. In contrast, in the paratenic poikilothermic host where metabolic pathways were moderately upregulated or silenced, larvae prepared for dormancy by triggering autophagy and longevity pathways. Identified differences and the modelling of handful of shared transcripts, provide the first insights into evolution of larval nematode virulence, warranting their further investigation as potential drug therapy targets.
Keywords: faktory virulence; Paratenic host; Anisakis; Rats; Accidental host; Larva; Anisakis spp.; Transcriptomics; Drug targets modelling; Fishes; Animals; anisakióza; krysa rodu Rattus; Virulence Factors; zvířata; ryby; Anisakiasis; larva